Sociodemographic status of rape victims in Dhaka Metropolitan area (Mediscope, 2018)
Our objective of the study was to find out the victims of common age group with relation to their educational and social status to set up a local and national policy to create nationwide awareness and taking necessary steps to stop this heinous crime. This is a cross-sectional descriptive type of study which was done in the Department of Forensic Medicine, Dhaka Medical College from January 2016 to December 2016 with maintaining ethical issues. A total of 69 cases, from 23 police stations of Dhaka Metropolitan area, were sent for a medicolegal opinion regarding forceful sexual intercourse and victims who ultimately agreed to do medicolegal examinations were examined and opinion was given, whether the signs of forceful sexual intercourse were present or not. Our study shows that female of >10-≥20 years of age group were the main victims and 69.6% of the victims belong to this age group followed by 14.5% with >20-≥30 years of age. Majority of the victims, 68.1% were from lower socioeconomic status. Educational knowledge of the victims was poor; 31.9% victims had the primary level of education, 24.6% were completely illiterate followed by 37.7% of victims had the education level as secondary and higher secondary, and 5.8% had the above higher secondary level. Victims of rape lead to very painful lives. They are just the victims of this heinous and supposed to get sympathy and empathy from the family, society, and state. But unfortunately, the victims of rape do not get proper attention from them. Sometimes victims are blamed by their surroundings. As a result, many victims commit suicide following rape. So, it should be addressed properly.Mediscope Vol. 5, No. 2: Jul 2018, Page 8-11